Predicting Narrative Essay Writing Ability through Grammar Awareness and Critical Thinking Skills: Evidence from Indonesian EFL Vocational High School Students - Aqila Thahira Sisfiamuhsha; Ismalianing Eviyuliwati; Alek Alek; Gelar Dwirahayu (Universitas Cokroaminoto Palopo, 2026)
This exploratory study examined the relationships among grammar awareness, critical thinking skills, and narrative essay writing ability among Indonesian EFL vocational high school students. Using a quantitative correlational design, data were collected from 35 tenth-grade students in one intact class at a vocational high school in Tangerang, selected through purposive sampling, using a grammar awareness test, a critical thinking test, and a narrative essay writing task, all validated through expert judgment and empirical testing. Data were analyzed using Pearson Product-Moment Correlation and Multiple Linear Regression. The results indicated significant positive correlations between grammar awareness and narrative writing ability (r = .649, p < .01) and between critical thinking skills and narrative writing ability (r = .687, p < .01). Grammar awareness and critical thinking skills jointly predicted narrative essay writing ability, explaining 54% of the variance (R² = .540, Adjusted R² = .511), with critical thinking emerging as the stronger predictor (β = .458) compared to grammar awareness (β = .347). Given the limited sample drawn from a single intact class, these findings should be interpreted as exploratory evidence rather than a broad generalization. Nonetheless, the results suggest that effective narrative writing draws on both linguistic competence and higher-order thinking skills. Accordingly, EFL writing instruction at the vocational level may benefit from integrating grammar instruction with activities that foster critical thinking.